Critical reflections on religion and media in contemporary Bali - Fox, Richard, 1972- (Numen Book Series, 2011)
Scholars of religion have always worked closely with media of one kind or another, from sacred books and archaic languages to cassette-sermons and the Internet. Yet comparatively little attention has been paid to the ways we actually use these and other media in the pursuit of historical inquiry. Drawing on ethnographic and archival research conducted on the Indonesian island of Bali, this book offers a critique of the media-related assumptions underpinning fields as diverse in their subject matter and approach as the history of religions, British cultural studies and Old Javanese philology. Its central contention is that more nuanced attention to problems of media will have serious implications for how we think about the study of religions, past and present.